Valve selection handbook engineering fundamentals for selecting the right valve design for every industrial flow application - Zappe, R. W., 1912-; Smith, Peter, 1951 June 7- (Amsterdam ; Boston : Elsevier : Gulf Professional Pub., 2004)
Valves are the components in a fluid flow or pressure system that regulate either the flow or the pressure of the fluid. They are used extensively in the process industries, especially petrochemical. Though there are only four basic types of valves, there is an enormous number of different kinds of valves within each category, each one used for a specific purpose. No other book on the market analyzes the use, construction, and selection of valves in such a comprehensive manner.-Covers new environmentally-conscious equipment and practices, the most important hot-button issue in the petrochemical industry today -Details new generations of valves for offshore projects, the oil industry's fastest-growing segment -Includes numerous new products that have never before been written about in the mainstream literature.
Introduction -- Fundamentals -- Manual valves -- Check valves -- Pressure relief valves -- Rupture discs -- Sizing pressure relief devices -- Actuators -- Double block and bleed ball valves -- Mechanical locking devices for valves.
Includes bibliographical references (p. 383-386) and index.
Keywords: Valves -- Handbooks, manuals, etc; Robinetterie (Appareils) -- Guides, manuels, etc; Electronic books